2010
DOI: 10.1002/bjs.7373
|View full text |Cite
|
Sign up to set email alerts
|

Multivisceral resection for primary locally advanced rectal carcinoma

Abstract: An aggressive surgical strategy with complete resection is predictive of long-term survival in selected patients with T4a rectal carcinoma. With optimal treatment local recurrence is a sign of systemic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
64
3
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(85 citation statements)
references
References 23 publications
(25 reference statements)
17
64
3
1
Order By: Relevance
“…It is difficult to distinguish the benefits of preoperative chemoradiotherapy, however, in patients with adjacent organ invasion. The use of preoperative treatment may contribute to an improved R0 resection rate, as in a recent British study where 25 of 33 patients who had an R0 total pelvic exenteration (TPE) had received preoperative treatment [17]. Additional treatment modalities may become more widely used in the multimodality approach to recurrent colorectal cancer.…”
Section: Neoadjuvantmentioning
confidence: 97%
See 3 more Smart Citations
“…It is difficult to distinguish the benefits of preoperative chemoradiotherapy, however, in patients with adjacent organ invasion. The use of preoperative treatment may contribute to an improved R0 resection rate, as in a recent British study where 25 of 33 patients who had an R0 total pelvic exenteration (TPE) had received preoperative treatment [17]. Additional treatment modalities may become more widely used in the multimodality approach to recurrent colorectal cancer.…”
Section: Neoadjuvantmentioning
confidence: 97%
“…Intraoperatively differentiating malignant invasion from benign adhesion is often impossible and dissecting through a malignant fistula, thereby violating tumour planes, is associated with tumour dissemination and adverse outcome. Thus, en bloc resection of involved adjacent organs is required to avoid dissemination and positive resection margins [17]. Lehnert et al [21] found the intraoperative accuracy of predicting a potentially curative operation was similar for colon (86%) and rectal (84%) cancer, for an overall accuracy rate of 85%.…”
Section: Stagingmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, treatment guidelines recommend multivisceral en bloc resection (MVEBR) for the treatment of clinically T4b tumors, as most studies have shown that MVEBR improves the rate of R0 resection, which is associated with better local control and overall survival 2,3. Neoadjuvant treatment (especially for rectal cancers) and complete resection, including en bloc resection of affected adjacent organs, is the standard clinical recommendation for patients with CRC.…”
Section: Introductionmentioning
confidence: 99%